A hysteresis model for timber joints with dowel-type fasteners. (15th February 2018) - Izzi, Matteo; Rinaldin, Giovanni; Polastri, Andrea; Fragiacomo, Massimo
Highlights: The hysteretic behaviour of timber joints with dowel-type fasteners is modelled. The behaviour of the steel and timber components is simulated using spring elements. The model employs simple mechanical relationships and basic input parameters. Shear tests are reproduced on nailed steel-to-timber joints used in CLT structures. The hysteretic behaviour and the energy dissipation under cyclic loads are analysed. Abstract: Predicting the mechanical behaviour and the failure mechanism of timber joints with dowel-type fasteners requires consideration of several factors, including the geometrical and mechanical properties of the metal fastener, the physical properties of timber and the interaction between such elements. This paper proposes a numerical model where a joint is schematized as an elasto-plastic beam in a non-linear medium with a compression-only behaviour. Unlike the differential approach adopted by most of the hysteresis models published in literature, this model predicts the load-displacement response using simple mechanical relationships and basic input parameters. Furthermore, the model is capable of reproducing the effect of the cavity formed around the fastener by timber crushing, and simulates the hysteretic behaviour and the energy dissipation under cyclic conditions. Shear tests are reproduced on nailed steel-to-timber joints in Cross-Laminated Timber and results are compared to the experimental test data obtained on similar single fastener joints. Simulations lead to accurate predictions of both the mechanical behaviour (initial stiffness, maximum load-carrying capacity, global shape of the loading curve and of the hysteresis cycles) and the total energy dissipation observed in the tests.